PPARα suppresses growth of hepatocellular carcinoma in a high-fat diet context by reducing neutrophil extracellular trap release - Banglun Pan; Zhu Zhang; Dongjie Ye; Xiaoxia Zhang; Yuxin Yao; Yue Luo; Haijie Hong; Xinran Cai; Yanling Chen; Nanhong Tang (JHEP Reports)
Background & Aims: The role of infiltrating neutrophils in hepatocellular carcinoma (HCC) is modulated by cellular metabolism, specifically lipid homeostasis. Throughout the progression of HCC, alterations in lipid metabolism are intricately linked with regulation of neutrophil function and the release of neutrophil extracellular traps (NETs). However, how much the protumor effect of a high-fat diet (HFD) depends on NETs and the potential interplay between NETs and other leukocytes in HCC remains uncertain. Methods: In this study, the molecular mechanism of NET release and the potential beneficial effects of PPARα agonists on the HCC microenvironment were explored through proteomics, metabolomics, tissue microarray, immunofluorescence, flow cytometry, western blot, and dual-luciferase reporter gene assays (n = 6 per group). Results: Our study demonstrated a notable inhibition of PPARα signaling in HCC. Furthermore, the disruption of PPARα-mediated lipid metabolism was responsible for the release of NETs. The presence of a HFD was observed to induce mitochondrial impairment in neutrophils, leading to the activation of cGAS-STING by oxidized mitochondrial DNA (Ox-mtDNA). Consequently, this activation triggered the release of NETs containing Ox-mtDNA through the enhancement of NLRP3-GSDMD-N in a NF-κB-dependent manner. Moreover, the release of NETs within HCC tissues effectively isolated cytotoxic leukocytes in the outer regions of HCC. Conclusions: Our study not only provides insight into the relationship between lipid metabolism disorders and NETs’ tumor-promoting function, but also provides an important strategic reference for multi-target or combined immunotherapy of HCC. Impact and implications:: We have identified PPARα and its agonists as therapeutic targets for controlling the neutrophil extracellular traps associated with high lipid metabolism. Results from preclinical models suggest that PPARα can limit mitochondrial oxidative stress, inhibit cGAS-STING-NF-κB signaling, and limit the release of neutrophil extracellular traps, thereby increasing the contact of anti-tumor leukocytes and hepatocellular cancer cells and limiting tumor growth.